Assessment of eating disorders - Mitchell, James E. (James Edward), 1947-; Peterson, Carol B. (Guilford Press, 2005)
Concise and practical yet comprehensive, this unique book provides a clear framework and a range of up-to-date tools for assessing patients with eating disorders. Leading clinicians and researchers describe the nuts and bolts of using diagnostic interviews, standardized databases, structured instruments, self-report and family-based measures, medical and nutritional assessment, a recently developed approach called "Ecological Momentary Assessment," and strategies for evaluating body image disturbance. Throughout, procedural guidelines are illustrated with concrete examples and sample forms, and a reproducible instrument (the Eating Disorder Questionnaire) is included. The book concludes with an integrative discussion of how to use assessment results in evidence-based treatment planning